Primary diagnosis of eosinophilic esophagitis in children in a surgical hospital - K.Y. Marakhouski; V.I. Averin; Y.A. Kaminskaya (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
The aim is to determine the criteria for the primary diagnosis and the features of the course of eosinophilic esophagitis (EoE) in children in a surgical hospital. Materials and methods. A retrospective analysis of inpatient records of 25 patients aged from 0 to 18 years who underwent inpatient treatment at the State Institution «Republican Scientific and Practical Center for Pediatric Surgery» from August 2017 to December 2019 for various nosological diseases with clinical esophageal manifestations. The data obtained was processed with the Microsoft Exel 2013 program. Results. The major criterion for diagnosing EoE is intraepithelial eosinophilic infiltration with eosinophil count in microscopy field of high resolution (×400) of at least 15 in one or several biopsy specimens. The number of biopsies from both proximal and distal esophagus should be at least 6 (the more biopsy samples, the higher the percentage of EoE diagnosis verification). All patients underwent esophagogastroduodenoscopy (EGD) with «ladder» biopsy from proximal and distal esophagus. For EGD the grading system for the endoscopic assessment of the oesophageal features of EoE described by Hirano et al. was used, which includes 5 major and 3 minor endoscopic features. The 5 major criteria for EOE assessment include: fixed rings, exudates plaques on the mucosa, vertical lines and longitudinal furrows, stricture, oedema; the 3 monor criteria include: transient and concentric rings, narrow calibre oesophagus, mucosal fragility. Conclusions. Eosinophilic esophagitis is more common in boys aged 5-7 and 10-17 years, aggravated by allergic history, with complaints of abdominal pain and dysphagia of unknown etiology. Esophagus biopsy is indicated in such patients. A biopsy should be performed for patients who were operated on for atresia of the esophagus, with dense anastomotic stenosis that appeared after a successful interval, as well as for children with a clinic of acquired esophageal stenosis; with a suspected diagnosis of achalasia if, according to esophageal manometry, this pathological condition does not apply to achalasia according to the Chicago classification and / or the stenosis zone is shifted upward from the lower esophageal sphincter; before corrective anti-reflux surgery (Nissen fundoplication) to reduce postoperative complications and to prevent worsening of the inflammatory process. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of all participating institution. The informed consent of the patient was obtained for conducting the studies.